Physicians' Perspectives on the Diagnosis and Treatment of Chronic Nonbacterial Osteomyelitis. (10th January 2017) - Zhao, Yongdong; Dedeoglu, Fatma; Ferguson, Polly J.; Lapidus, Sivia K.; Laxer, Ronald M.; Bradford, Miranda C.; Li, Suzanne C.
Abstract : Background/Purpose . Understanding the practices of pediatric rheumatologists in diagnosing and treating chronic nonbacterial osteomyelitis (CNO) can provide important information to guide the development of consensus treatment plans. The objectives of this study were to determine physicians' approaches to (1) diagnosing and monitoring CNO, (2) ordering a bone biopsy, and (3) making treatment decisions. Methods . A survey was distributed among members of the Childhood Arthritis and Rheumatology Research Alliance using a web-based questionnaire. Results . 121 of 277 (41%) attending physician members completed the survey. Plain radiographs (89%) were most commonly used followed by regional MRI (78%), bone scintigraphy (43%), and whole-body MRI (36%). The top three reasons for performing a biopsy were constitutional findings (66%), unifocal bone lesions (64%), and nocturnal bone pain (45%). Nearly all responders (95%) prescribed nonsteroidal anti-inflammatory drugs (NSAIDs) as initial therapy. For patients who failed NSAID treatment, methotrexate (67%), tumor necrosis factor inhibitors (65%), and bisphosphonates (46%) were the next most commonly used treatments. The presence of a spinal lesion increased the use of bisphosphonate treatment. Conclusion . The diagnostic approach and disease activity monitoring for CNO varied among surveyed physicians. Our survey findings provided important background for the development of consensus treatment plans for CNO.